Acute Urticaria and Anaphylaxis: Differences and Similarities in Clinical Management - Ensina, Luis Felipe; Min, Taek Ki; Félix, Mara Morelo Rocha; de Alcântara, Carolina Tavares; Costa, Célia (Frontiers in Allergy, 2022)
Acute urticaria is a common condition that presents with wheals and/or angioedema. However, these symptoms are also frequent in anaphylaxis, a life-threatening reaction that should be immediately diagnosed and treated. In both, mast cells play a central role in the physiopathology. Causes and triggers of acute urticaria and anaphylaxis are similar in general, but some peculiarities can be observed. The diagnostic approach may differ, accordingly to the condition, suspicious causes, age groups and regions. Adrenaline is the first-line treatment for anaphylaxis, but not for acute urticaria, where H1-antihistamines are the first choice. In this paper, we review the main aspects, similarities and differences regarding definitions, mechanisms, causes, diagnosis and treatment of acute urticaria and anaphylaxis.